Suction diathermy adenoidectomy: audit of current practice in a tertiary care hospital - Venkataramani, Nithya; Sachidananda, Ravi; Dachuri, Sandeep; Vasishta, Srividya Rao (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Adenoidectomy is conventionally performed using adenoid curette as a blind procedure. Suction diathermy adenoidectomy is a technique of ablating the adenoid tissue using thermal energy and removing it by suction. This audit aims to study the efficacy and complications of this technique in a tertiary care center. Methods: Retrospective analysis of hospital database was conducted. Twenty-seven patients who underwent suction diathermy adenoidectomy were identified and hospital records studied. Parents were contacted and enquired regarding improvement in child’s symptoms. Results: No instances of postoperative complications identified. All except 2 parents were completely satisfied with the improvement in their child’s symptoms. Two children had occasional mouth breathing. Conclusions: Suction diathermy adenoidectomy is a feasible alternative to conventional adenoidectomy with few complications and minimal rate of recurrence.